UPAYA PENCEGAHAN KEJAHATAN TERPADU TERHADAP PELANGGARAN DAERAH PENANGKAPAN IKAN - Kurniadi Dwiyanto (Jurnal Kriminologi Indonesia, 2017)
This article discusses about the community involvement in the efforts to prevent fishingground violations and conflict prevention efforts as a form of integrated crime preventionin Indonesia. Fishing ground violation, as an act of illegal fishing, occurs due to high fishdemand that is accompanied by limited resources of state institutions to oversight andthe presence of corrupt officers in prosecution stage. Conflicts among fishermen emergedas the consequences. There is a research in criminology studies in Indonesia previouslydiscussed about community involvement in the prevention of destructive fishing. While thispaper discusses it in the context of fishing ground violation. Community involvement in thesurveillance of Indonesian fishery activities is implemented through the establishment of aPublic Oversight System that has been regulated in the Regulation of the Minister of MarineAffairs and Fisheries. The goal is to overcome the lack of official agencies in conductingsurveillance in the field. This paper seeks to explain the motivation of community involvementusing the theory of social exchange. Providing recommendations on the passage of communityinvolvement in the prevention of violations of fishing grounds will also be discussed in this paper.